Video Implementation in Learning English in Class VIII MTs Al-Hasanah Islamic Boarding School Bengkulu Tengah - Iniartini Iniartini; Henny Herlina; Kasiati Kasiati (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2023)
The Implementation of video in Teaching and Learning Process at Class VIII of MTS Ponpes Al-Hasanah Bengkulu Tengah. This research aims to know the use of video in teaching and learning process in MTS Ponpes Al-Hasanah Bengkulu Tengah. The research applied quantitative approach by using questionnaires. The questionnaires shared by 41 students of class VIII containing 5 questions. Based on the data, it was obtained that 59% answered that the video was never used during teaching and learning. 63% of the were interested if video would be used in future learning. They also agreed that the video would make them easily understand English.